An IDENTIFIKASI KETERDAPATAN POTENSI BAHAN GALIAN PASIR KUARSA DI KELURAHAN PADANG, KECAMATAN SUKAMARA, KABUPATEN SUKAMARA - Desyana Ghafarunnisa; Gingga, Flaminggo; Kurniawan , Angga (JURNAL SIMETRIK, 2025)
Quartz sand plays a vital role in various industries due to its unique properties and practical applications. Sukamara Regency is one of the regions with widespread quartz sand distribution. This research was conducted in Teluk Madang, Padang Sub-district, Sukamara District, Sukamara Regency, Central Kalimantan Province. The objectives of this study are to determine the distribution and thickness of quartz sand in the study area and to estimate its resource potential. The research method involved direct field observation, which was then processed into spatial data and resource calculation using the polygon method. Based on the regional geological map of the Pangkalan Bun sheet, the area comprises three geological formations: the Dahor Formation (TQd), Alluvial Deposits (Qa), and Mud Deposits (Qs), all of which show potential for quartz sand accumulation. Geomorphological observations identified three landform units: alluvial plains (51%), swampy lowlands (20%), and undulating terrain (29%). A total of 96 hand-drilled boreholes were carried out across the study area, which covers 4.62 hectares. The thickest quartz sand layer recorded was 3.6–4 meters, while the thinnest was 0.4 meters. The average thickness ranged from 1.3 to 1.8 meters. Using the polygon method, the estimated volume of quartz sand resources is 12,225 m³. With a density of 2.6 g/cm³, the total estimated tonnage of silica sand in the 4.62-hectare study area is approximately 31,785 tons. Keywords: Quartz sand, Sukamara Regency, resource estimation, polygon method, geological formation, geomorphology.